2016
DOI: 10.18632/oncotarget.10010
|View full text |Cite
|
Sign up to set email alerts
|

Integrating heterogeneous drug sensitivity data from cancer pharmacogenomic studies

Abstract: The consistency of in vitro drug sensitivity data is of key importance for cancer pharmacogenomics. Previous attempts to correlate drug sensitivities from the large pharmacogenomics databases, such as the Cancer Cell Line Encyclopedia (CCLE) and the Genomics of Drug Sensitivity in Cancer (GDSC), have produced discordant results. We developed a new drug sensitivity metric, the area under the dose response curve adjusted for the range of tested drug concentrations, which allows integration of heterogeneous drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 13 publications
1
45
0
Order By: Relevance
“…They further showed that increased fetal bovine serum and seeding cell density had a systematic effect on mean cell viability. Pozdeyev et al showed that restricting the computation of AUC to the concentration range shared between GDSC and CCLE, the equivalent of our AUC* drug sensitivity measure, yielded a small, but statistically significant improvement in consistent of pharmacological profiles 28 . Ultimately what our analysis and these recent reports suggest is that not only drug sensitivity measurements must be carefully and appropriately compared, but also that there is a pressing need for more robust pharmacological assays and standardized computational methods for modeling drug response.…”
Section: Discussionmentioning
confidence: 94%
“…They further showed that increased fetal bovine serum and seeding cell density had a systematic effect on mean cell viability. Pozdeyev et al showed that restricting the computation of AUC to the concentration range shared between GDSC and CCLE, the equivalent of our AUC* drug sensitivity measure, yielded a small, but statistically significant improvement in consistent of pharmacological profiles 28 . Ultimately what our analysis and these recent reports suggest is that not only drug sensitivity measurements must be carefully and appropriately compared, but also that there is a pressing need for more robust pharmacological assays and standardized computational methods for modeling drug response.…”
Section: Discussionmentioning
confidence: 94%
“…In summary, as others have reported (30), discrepancies in the AUC measurements between the two studies is the major factor contributing to discordant observations. Despite this, we conclude that the majority of significant correlations that we report here are valid.…”
Section: Concordance Between the Two Datasetsmentioning
confidence: 60%
“…the area over the graph of relative growth inhibition vs. drug concentration. Previous studies based on CCLE data found that this metric was one of the most informative 31,[40][41][42] , so we adopted it for our analysis. Two sources of information were available to quantify the genetic load: copy number changes and point mutations.…”
Section: Resultsmentioning
confidence: 99%
“…CCLE generated eight-point dose-response curves for each of the 24 compounds using an automated compound-screening platform 31 . We used the drug activity area as a measure of drug response because previous studies found it most informative 31,[40][41][42] .…”
Section: Ccle Datamentioning
confidence: 99%